Sustaining Key Skills in the UK Military Aircraft Industry - Bassford, Matt (RAND Corporation, 2010)
The United Kingdom Ministry of Defence's Fixed Wing Sector Strategy Board commissioned RAND Europe to assist in the development of a strategy and sustainment plan for the military fixed wing sector. RAND focused on the health and sustainment of key skills in the sector's industrial base. This monograph describes the qualitative and quantitative methodologies that the RAND team followed and summarises its findings and recommendations.